Characterization of a non-human primate model for the study of testicular peritubular cells—comparison with human testicular peritubular cells. (29th May 2018) - Schmid, N; Stöckl, J B; Flenkenthaler, F; Dietrich, K -G; Schwarzer, J U; Köhn, F -M; Drummer, C; Fröhlich, T; Arnold, G J; Behr, R; Mayerhofer, A
Abstract: STUDY QUESTION: Are monkey testicular peritubular cells (MKTPCs) from the common marmoset monkey ( Callithrix jacchus ) a suitable translational model for the study of human testicular peritubular cells (HTPCs)? SUMMARY ANSWER: MKTPCs can be isolated and propagated in vitro, retain characteristic markers for testicular peritubular cells and their proteome strongly (correlation coefficient of 0.78) overlaps with the proteome of HTPCs. WHAT IS KNOWN ALREADY: Smooth-muscle-like peritubular cells form the wall of seminiferous tubules, transport sperm, are immunologically active, secrete a plethora of factors and may contribute to the spermatogonial stem cell niche. Mechanistic studies are hampered by heterogeneity of human samples. STUDY DESIGN, SIZE, DURATION: We established a culture method for MKTPCs and characterized these cells from six young adult animals (2–3 years). To examine whether they qualify as a translational model we also examined HTPCs from seven men and compared the proteomes of both groups. PARTICIPANTS/MATERIALS, SETTING, METHODS: We used explant cultures to obtain MKTPCs, which express smooth muscle markers (calponin ( CNN1 ), smooth muscle actin ( ACTA2 )), lack FSH-receptors ( FSHR ) and LH-receptors ( LHCGR ), but possess androgen receptors ( AR ). MKTPCs can be passaged at least up to eight times, without discernable phenotypic changes. Mass-spectrometry-based analyses of the MKTPC and HTPC proteomes were performed. MAIN RESULTS AND THE ROLE OF CHANCE: We established a method for isolation and cultivation of MKTPCs, and provide a comprehensive analysis of their protein repertoire. The results let us conclude that MKTPCs are suitable as a non-human primate model to study peritubular cell functions. LARGE SCALE DATA: List of identified proteins in MKTPCs by liquid chromatography–tandem mass spectrometry is accessible at the ProteomeXchange (identifier PXD009394). LIMITATIONS, REASON FOR CAUTION: This is an in vitro cellular non-human primate model used to provide a window into the role of these cells in the human testis. WIDER IMPLICATIONS OF THE FINDINGS: Previous studies with HTPCs from patients revealed a degree of heterogeneity, possibly due to age, lifestyle and medical history of the individual human donors. We anticipate that the new translational model, derived from young healthy non-human primates, may allow us to circumvent these issues and may lead to a better understanding of the role of peritubular cells. STUDY FUNDING AND COMPETION OF INTEREST(S): This work was supported by grants from the Deutsche Forschungsgemeinschaft (MA 1080/27-1; AR 362/9-1; BE 2296/8-1). The authors declare no competing financial interests.